STRUKTUR NALAR TEOLOGI ISLAM PERSPEKTIF JOSEF VAN ESS; ANALISA ATAS ORISINILITAS DAN KETERPENGARUHAN NALAR KALA>M - Purnama, Fahmy Farid (Dialogia: Jurnal Studi Islam dan Sosial, 2015)
Abstract: At the beginning, the development of kala>m tradition is to understand the activity of ‘thinking’ as a 'discussion', not an effort to 'proving' logically (demonstration). So the logical structure of Islamic theology functions as activities rhetorical-dialectic (dialectical theology). Rapidly, Kalam discourse intersection with Aristotle syllogism has brought a new dynamic in the face of Islamic theology. Although the development of logical structure of Islamic theology is quite dynamic, but according to Josef van Ess, the philosophy of Aristotle had never really 'conquered' the influence of Stoicism in designing Islamic theology. Discourse kala>m always confined within the framework of baya>ni. Kalam is being stuck in nalar baya>ni itself get various lawsuits. Qiya>s baya>ni considered cannot explain inimitable (incomparable) at all, the reality of God. Epistemology study about kala>m done by Josef van Ess, gives an understanding that Islamic tradition has a distinctive character of its rationality. Thus, assuming no growth of rationality in Islam refuted itself. Nevertheless, kala>m cannot be separated from the affect of various shades of reasoning that develops in timeKeywords: Kala>m, Mantiq (logika), Analogi, Silogisme, `Illat (middle term) dan  Stoikisme